2006
DOI: 10.1002/ejsp.404
|View full text |Cite
|
Sign up to set email alerts
|

Rational model and justification model in ‘outcome bias’

Abstract: The authors of this study suggest that the harm-punishment link ('outcome bias') can be explained by the activation of different judgment processes depending on the outcome severity of an offense: (1) a rational model for mild outcomes in which punishment is necessarily linked to responsibility of the perpetrator; (2) a justification model for severe outcomes in which punishment and responsibility are linked only when assessment order allows the latter to rationalize the former. Participants (126 university st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Other work corroborates this, finding that outcomes are viewed as more predictable in retrospect ("a reasonable person should have expected that"), which leads to greater condemnation when the outcome is bad ( Baron and Hershey 1988;Tostain and Lebreuilly 2008). Specifically, she found that adults judged an agent whose careless action lead to a worse outcome to be more responsible than an agent who caused a mildly bad outcome.…”
Section: Hindsight Biasmentioning
confidence: 80%
See 1 more Smart Citation
“…Other work corroborates this, finding that outcomes are viewed as more predictable in retrospect ("a reasonable person should have expected that"), which leads to greater condemnation when the outcome is bad ( Baron and Hershey 1988;Tostain and Lebreuilly 2008). Specifically, she found that adults judged an agent whose careless action lead to a worse outcome to be more responsible than an agent who caused a mildly bad outcome.…”
Section: Hindsight Biasmentioning
confidence: 80%
“…This explanation is often referred to as hindsight bias, because it attributes clairvoyant caution with the benefit of hindsight (Baron and Hershey 1988;Tostain and Lebreuilly 2008; see also Alicke and Davis 1989;Mazzocco, Alicke, and Davis 2004;Young, Nichols, and Saxe 2010). Here, we focus in particular on resultant luck, or luck in the way things turned out.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond their implications for our understanding of behavioral control as a criterion for moral judgment, our results speak to a larger debate over the mechanisms underlying moral luck and its influence on punishment. Previous psychological research has characterized moral luck in terms of outcome bias (Alicke & Davis, 1989;Carlsmith, Darley, & Robinson, 2002;Darley, Carlsmith, & Robinson, 2000) or hindsight bias (Baron & Hershey, 1988;Tostain & Lebreuilly, 2008;Young et al, 2010). According to the outcome bias model, the mere presence of a bad outcome generates negative affect in the perceiver, which subsequently biases moral judgment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior work on hindsight bias has shown such an influence (Baron & Hershey, 1988;Tostain & Lebreuilly, 2008;Young, Nichols, & Saxe, 2010 Figure 2). As intended by our manipulation, we found that participants attributed greater control to the agent who chose between two available options compared with the agent who was forced to -choose‖ the only available option.…”
Section: Experiments 2amentioning
confidence: 93%
“…In our example above and starting with the indirect effect (via hindsight bias), such an effect would be present if the outcome feedback first led to exaggerated impressions of the foreseeability of a fatal outcome and these in turn to negative evaluations of the decision to perform the operation and of the surgeon's competence. A direct effect of outcome knowledge (outcome bias) would be present if observers let their evaluations be influenced by the outcome irrespective of any associated foreseeability impressions, for example in an effort to restore a sense of justice by ‘punishing’ the surgeon for the fatal outcome (Alicke, ; Tostain & Lebreuilly, ). The precise nature of the reasons, justifications, or more generally processes involved in direct outcome effects depends of course on the specific context of a case, but there are two essential requirements that distinguish them from the previously discussed indirect effects: (1) that they bypass any hindsight‐related cognitions and (2) that they are driven by outcome valence , not by outcome knowledge per se .…”
Section: Introductionmentioning
confidence: 99%